The study of Tokopedia re-purchase intention during Covid-19 pandemic - Putri Permata Sari; Filda Rahmiati (President University, 2022)
This study aims to determine the impulsive behaviour using a brand image, brand ambassadors, service quality, and customer satisfaction on Tokopedia re-purchase intention. In this study, a quantitative approach was used to collect data from an online questionnaire (Google Form) for the Tokopedia users who had made a transaction more than once. The online questionnaire was distributed via social media and received 145 valid responses, with PLS-SEM being used to analyze the hypothesis testing of this research. The result shows that brand image indirectly influences the re-purchase intention of Tokopedia mediated by impulsive behaviour. The brand ambassador also has an indirect influence on the re-purchase intention of Tokopedia mediated by customer satisfaction and impulsive behaviour, and service quality has a direct and indirect influence on the re-purchase intention of Tokopedia mediated by customer satisfaction. Furthermore, customer satisfaction and impulsive behaviour have a significant influence on the re-purchase intention of Tokopedia. Tokopedia must pay attention to factors interested in re-purchase intention, which means that Tokopedia should maintain service quality and customer satisfaction and improve customers' experience when customers make impulsive behaviour.